2020
DOI: 10.1016/j.hlpt.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Reframing egg donation in Europe: new regulatory challenges for a shifting landscape

Abstract: The first birth from a donated egg was reported in Australia in 1984, ushering in a new era of possibilities for the treatment of infertility (1). Since then egg donation has undergone a number of technical, regulatory and commercial transformations. Its use by a growing and diverse range of social groups and more recently the dawn of advanced freezing technologies, have reconfigured the process. Given the transformation in its organisation and practice, there is a pressing need to map these changes in finer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…First, even if we have focused on the local level, both cases are part of global networks. Egg provision functions on a global scale, and this has an effect in Spain by having people from abroad coming to Spain to do the treatments, by having providers with specific nationalities or read as phenotypically desirable donating in Spain, as has already been studied (Nahman 2018) and as we saw in our analysis above, and by the recent expansion of exportation practices thanks to the success of egg vitrification and the formation of egg banks (Hudson et al 2020). Still, domestic employment still provides work for many migrant women in Spain, particularly those coming from Latin America.…”
Section: Concluding Remarks: the Stratification Of Access To Solving mentioning
confidence: 71%
“…First, even if we have focused on the local level, both cases are part of global networks. Egg provision functions on a global scale, and this has an effect in Spain by having people from abroad coming to Spain to do the treatments, by having providers with specific nationalities or read as phenotypically desirable donating in Spain, as has already been studied (Nahman 2018) and as we saw in our analysis above, and by the recent expansion of exportation practices thanks to the success of egg vitrification and the formation of egg banks (Hudson et al 2020). Still, domestic employment still provides work for many migrant women in Spain, particularly those coming from Latin America.…”
Section: Concluding Remarks: the Stratification Of Access To Solving mentioning
confidence: 71%
“…This paper draws on methods of critical reflection ( Hauskeller and Beltrame, 2016 , Hudson et al, 2020 ), which involves examination of the implications of a social phenomenon by drawing and reflecting on existing published findings and theoretical concepts. It begins by examining the historical and political situatedness of ignorance around women’s bodies and health in the context of androcentric biomedicine, exploring via existing literature how this context shaped the ‘discovery’ and definition of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…It considers how endometriosis has been 'willfully ignored' (Tuana, 2006), and therefore proposes that knowledge about endometriosis has been inhibited by underinvestment in scientific research, despite the fact that it has been identified as worthy of policy attention and scientific research by women who are affected (Frickel et al, 2010). This paper draws on methods of critical reflection (Hauskeller and Beltrame, 2016;Hudson et al, 2020), which involves examination of the implications of a social phenomenon by drawing and reflecting on existing published findings and theoretical concepts. It begins by examining the historical and political situatedness of ignorance around women's bodies and health in the context of androcentric biomedicine, exploring via existing literature how this context shaped the 'discovery' and definition of endometriosis.…”
mentioning
confidence: 99%
“…IVF treatment involving the use of donated eggs now accounts for 7% of all treatment globally, and the number of cycles increases annually (Banker et al., 2021 ). A number of recent technical and commercial transformations have reshaped how eggs are retrieved, stored and managed (Hudson et al., 2020 ; Waldby, 2019 ). Alongside these shifts, differences in how egg donation is framed as a social, economic and moral practice have emerged, accompanied by a global patchwork of related policies.…”
Section: Introductionmentioning
confidence: 99%